2009
DOI: 10.1097/aud.0b013e31818fbb7a
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Tuning Curves Derived from Auditory Steady State Evoked Potentials: A Proof-of-Concept Study

Abstract: Objectives: Assess the feasibility of drawing tuning curves from the masking function of steady state potentials. Develop a noninvasive tool for research applications on cochlear frequency selectivity in sedated animais. Obtain pilot human data validating auditory steady state evoked potential-derived (ASSEP) tuning curves against psychophysical data.,.Design: ASSEP tuning curves were drawn in 10 Beagle puppies and six human adults using amplitude-modulated probes. Two probe frequencies (1 and 2 kHz) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…The fact that we found a close relationship between mean PTCs and mean SFOAE STCs suggest that the former are to a large extent shaped by cochlear mechanics (e.g., Pickles 1979;Evans 2001). This view is also supported by a good agreement between our estimates of sharpness of tuning and those obtained with evoked potential tuning curves (Eggermont 1977;Harrison et al 1981;Harrison 1984;Markessis et al 2009). …”
Section: The Shape Of Sfoae Stcs and Phase Effects-implications For Ssupporting
confidence: 86%
“…The fact that we found a close relationship between mean PTCs and mean SFOAE STCs suggest that the former are to a large extent shaped by cochlear mechanics (e.g., Pickles 1979;Evans 2001). This view is also supported by a good agreement between our estimates of sharpness of tuning and those obtained with evoked potential tuning curves (Eggermont 1977;Harrison et al 1981;Harrison 1984;Markessis et al 2009). …”
Section: The Shape Of Sfoae Stcs and Phase Effects-implications For Ssupporting
confidence: 86%
“…It remains unclear how sweep direction or general differences between measurement paradigms would lead to disagreements only at 4000 Hz but not at the remaining signal frequencies. Similarly, our data are in good agreement with Q 10 s of PTCs recorded with either traditional or fast methods at corresponding masker bandwidths for 1000 and 2000 Hz, but at 4000 Hz our subjects appear to have narrower curves (Kluk & Moore, 2004; Malicka et al, 2009; Markessis et al, 2009). Thus, it is most plausible that the observed differences at 4000 Hz reflect individual differences in frequency selectivity.…”
Section: Discussionsupporting
confidence: 85%
“…The difference in tuning was caused by greater susceptibility of GN-PTC method to training effects, because the run 2 curves had widths comparable to GN-AM-PTC (Table 2). Accordingly, amplitude modulating the probe does not affect the PTC width (Markessis et al, 2009), but it makes the task easier when combined with a gated-noise masker. This conclusion is also supported by the substantially lower rejection rate of PTCs in the GN-AM-PTCs condition as compared to GN-PTCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markessis et al (2009) estimated ETC-tip frequencies in normally hearing subjects by recording ASSR thresholds in the presence of masking noise. They found that the tips of the ASSR ETCs were often shifted to frequencies higher than the signal, which they referred to as detuning.…”
Section: Introductionmentioning
confidence: 99%